Uma abordagem para a verificação do comportamento excepcional a partir de regras de designe e testes - Sales Junior, Ricardo José (2013)
Checking the conformity between implementation and design rules in a system is an important activity to try to ensure that no degradation occurs between architectural patterns defined for the system and what is actually implemented in the source code. Especially in the case of systems which require a high level of reliability is important to define specific design rules for exceptional behavior. Such rules describe how exceptions should flow through the system by defining what elements are responsible for catching exceptions thrown by other system elements. However, current approaches to automatically check design rules do not provide suitable mechanisms to define and verify design rules related to the exception handling policy of applications. This paper proposes a practical approach to preserve the exceptional behavior of an application or family of applications, based on the definition and runtime automatic checking of design rules for exception handling of systems developed in Java or AspectJ. To support this approach was developed, in the context of this work, a tool called VITTAE (Verification and Information Tool to Analyze Exceptions) that extends the JUnit framework and allows automating test activities to exceptional design rules. We conducted a case study with the primary objective of evaluating the effectiveness of the proposed approach on a software product line. Besides this, an experiment was conducted that aimed to realize a comparative analysis between the proposed approach and an approach based on a tool called JUnitE, which also proposes to test the exception handling code using JUnit tests. The results showed how the exception handling design rules evolve along different versions of a system and that VITTAE can aid in the detection of defects in exception handling code